Hermeneutika Al-Qurtubi: - Isnaini, Subi Nur (SUHUF, 2022)
This article aims to examine the influence of Ibn Atiyyah (d. 451 H) to al-Qurtubi (d. 671 H) in the al-Jami' li Ahkam al-Qur'an. Tafsir al-Qurtubi is one of the most well-known interpretations that referred to in the Islamic scientific tradition. This research is a qualitative research using analytical descriptive method. This research is library research and taking the book of al-Jami' li Ahkam al-Qur'an and al-Muharrar al-Wajiz as primary sources. This article departs from the necessity of being influenced in every thought and science. Every interpreter must be in certain situations that can affect his understanding of the interpreted text, or in Gadamer's hermeneutics it is called historically effected consciousness. This article finds that the influence of al-Qurtubi from Ibn Atiyyah is very strong, both in the methodological and thought aspect. The influence of Ibn Atiyyah in the interpretation of al-Qurtubi can be seen from the many opinions and thoughts of Ibn Atiyyah that adopted by al-Qurtubi in his interpretation, both from the aspect of bi al-ma'sur interpretation, qira'at aspects, grammatical nahwu, balagah, fiqh and Islamic law. In addition, in several respects, al-Qurtubi also discussed, commented on, and criticized Ibn Atiyyah's opinion in al-Muharrar al-Wajiz.